Activities and programmes that support the emotional wellness and well-being of refugees, immigrants and other newcomers within settlement agencies: a scoping review protocol. Issue 9 (16th September 2020) - Goopy, Suzanne; Suva, Cesar; Hayden, K. Alix; Silversides, Halley; Palova, Katerina
Abstract : Introduction: Obstacles to successful settlement—social isolation, language hardship, issues with employment, housing questions, transportation, barriers to health, education and government service access—all potentially play a role in emerging physical and mental health problems. The objective of this scoping review is to map the available evidence in order to provide an overview of the services and resources offered to refugees, immigrants and other newcomers by settlement agencies to support emotional wellness and well-being. Methods and analysis: The protocol to be followed for this scoping review is based on the Joanna Briggs Institute to provide a map of the current and emergent literature, and examine the extent, range and nature of this literature. The proposed scoping review will also identify the gaps in research pertaining to the emotional wellness of refugees, immigrants and other newcomers as well as summarise and disseminate research findings and provide direction for future reviews. Key databases for this scoping review include APA PsycINFO, Medline, Embase, Cumulative Index of Nursing and Allied Health Literature Plus, Academic Search Complete, and Education Research Complete. The database search start and end dates for this scoping review will be from inception to July 2020. The article searches will take place between August and October 2020. Ethics and dissemination: Ethics is not required as the research will not involve human or animal subjects. The research is a scoping review, and thus relies on published and grey literature studies and documents. The findings of this proposed scoping review will be disseminated through future publications as well as presentations to relevant stakeholders, including immigrant serving agencies. We anticipate that this scoping review will identify gaps in research pertaining to the emotional wellness of refugees, immigrants and other newcomers. The results of this review will be the first comprehensive recent survey of emotional wellness practices employed by settlement agencies.